2020
DOI: 10.1016/j.frl.2020.101748
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and stock market volatility: An industry level analysis

Abstract: Highlights This paper analyzes the effects of COVID-19 on the U.S. stock market volatility at the industry level. The market switching AR model is used to identify regime change from lower volatility to higher volatility. Petroleum and natural gas, restaurants, hotels and lodgings industries exhibit large increases in risk. Machine learning (ML) feature selection methods are used to identify influential economic indicators. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
311
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 429 publications
(341 citation statements)
references
References 26 publications
24
311
0
6
Order By: Relevance
“…The results of the study further connected with the findings of the subsequent studies that concluded that financial trading is affected due to increase COVID-19 infected cases (see, Erdem 2020;Baek et al 2020;Chia et al 2020). These studies highlighted the need to subsidize the financial and healthcare sector to marginalize coronavirus's adverse effects in economic and business processes.…”
Section: Resultssupporting
confidence: 81%
“…The results of the study further connected with the findings of the subsequent studies that concluded that financial trading is affected due to increase COVID-19 infected cases (see, Erdem 2020;Baek et al 2020;Chia et al 2020). These studies highlighted the need to subsidize the financial and healthcare sector to marginalize coronavirus's adverse effects in economic and business processes.…”
Section: Resultssupporting
confidence: 81%
“…As the World Health Organization (WHO), news media, and other non-profit organizations continue to provide the daily number of cases and deaths from COVID-19, our study contributes to the literature by exploring whether and how the stock market returns, volatility, and trading volume were affected by the percentages of daily cases and deaths from COVID-19 throughout 76 countries stock indices. Our study also extends current literature that mostly focuses on either developed countries (i.e., Baek et al, 2020 ; Salisu & Akanni, 2020 ; Zhang et al, 2020 ) or emerging countries (i.e., Haroon & Rizvi, 2020 ; Mishra et al, 2020 ) by conducting a direct comparison of the impact of COVID-19 on 53 emerging countries and 23 developed countries.…”
Section: Discussionmentioning
confidence: 51%
“…Recent studies have also examined the impact of COVID-19 on the equity markets’ volatility and trading volume. Baek, Mohantry, and Glambosky (2020) find a significant increase in absolute risk for the US equity market due to the COVID-19 deaths. Salisu and Akanni (2020) construct a global fear index (GFI) based on the cases and deaths from the COVID-19.…”
Section: Literature Review and Hypothesesmentioning
confidence: 91%
“…COVID-19 has been a worldwide pandemic since March 2020, which will greatly affect asset price. Existing studies have focused on the impact of COVID-19 on the financial asset price such as the US Treasuries ( He et al., 2020 ), sovereign Eurobonds ( Sene et al., 2020 ), corporate bonds ( Haddad et al., 2020 ; Kargar et al., 2020 ), and stocks ( Baek et al., 2020 ; Gormsen and Koijen, 2020 ; Just and Echaust, 2020 ). However, there is a lack of research linking COVID-19 and housing price.…”
Section: Introductionmentioning
confidence: 99%